AN INVESTIGATION OF THE MANAGERIAL EFFECTIVENESS IN PEOPLE MANAGEMENT OF UNIT MANAGERS AT PRIVATE NURSINGHOME - Deng, Liang (2009)
In the last two decades, more and more nursing homes have been established in the western counties. Then, a number of issues related to managerial effectiveness within nursing home have been conducted by scholars and researchers. As far as the author have a part-time job in a private nursing home, in addition, he has such genuine interest in the behavior of middle level managers within organizations that how they could manage the lower level workers successfully and effectively.